2018
DOI: 10.1111/acer.13923
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Binge‐Like and Aversion‐Resistant Alcohol Drinking in C57BL/6J Mice

Abstract: BackgroundAlcohol use disorder is characterized by compulsive alcohol intake, or drinking despite negative consequences. Previous studies have shown that female rodents have a heightened vulnerability to drug use across different stages of the addictive cycle, but no previous studies have studied females in a model of aversion‐resistant alcohol intake. Here, we investigated sex differences in binge‐like and aversion‐resistant alcohol drinking in C57BL/6J mice using a modified drinking‐in‐the‐dark (DID) paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
98
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 53 publications
28
98
1
Order By: Relevance
“…These observations are consistent with previously reported findings with mouse DID models using other delivery vehicles and paradigms (Lyons et al, 2008;Moore et al, 2010;Rhodes et al, 2007). Moreover, female mice in the study consumed significantly greater quantities of EtOH than male mice during each DID episode (Figs 2 and 3), a phenomenon consistent with that reported by Crabbe and others (Crabbe et al, 2009;Rhodes et al, 2005;Sneddon et al, 2019).…”
Section: Sex-specific Difference In Binge Etoh Intakesupporting
confidence: 93%
“…These observations are consistent with previously reported findings with mouse DID models using other delivery vehicles and paradigms (Lyons et al, 2008;Moore et al, 2010;Rhodes et al, 2007). Moreover, female mice in the study consumed significantly greater quantities of EtOH than male mice during each DID episode (Figs 2 and 3), a phenomenon consistent with that reported by Crabbe and others (Crabbe et al, 2009;Rhodes et al, 2005;Sneddon et al, 2019).…”
Section: Sex-specific Difference In Binge Etoh Intakesupporting
confidence: 93%
“…Sex differences in alcohol intake and preference are well recognized in animals and humans, with females generally drink more alcohol than males [30][31][32][53][54][55]. Consistent with this, average daily alcohol intake in female Bmal1CTR mice was significantly greater than in Bmal1CTR males (P<0.0001, unpaired two-tailed t test) and mean alcohol preference was significantly higher in Bmal1CTR females than Bmal1CTR males (P<0.05, unpaired two-tailed t test) ( Supplementary Fig.…”
Section: Deletion Of Bmal1 or Per2 From Msns Eliminates Sex Differencsupporting
confidence: 66%
“…As self‐administration is known to induce distinct patterns of behavior and neurobiological alterations when compared to experimenter administered drugs and alcohol, (McFarland et al., , ; Moolten and Kornetsky, ; Robinson et al., ), this may explain some of the discrepancies observed between these studies. Relatedly, the findings indicating a lack of sex differences in consumption of quinine‐adulterated EtOH were in mice that exclusively self‐administered alcohol (Sneddon et al., ). It is possible that the sex differences observed in our findings in part result from experimenter administration of EtOH and/or restriction to the rewarding effects of postingestive EtOH.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating compulsive‐like EtOH seeking includes a number of models, involving punished operant self‐administration and consumption of quinine‐adulterated EtOH (Darevsky et al., ; Hopf and Lesscher, ; Radke et al., ). Recent research has identified similar sensitivities to quinine adulteration in males and females, suggesting that sex differences are not present in this form of inflexible EtOH taking (Sneddon et al., ). Importantly, in both punished self‐administration and quinine adulteration models, the experience of reward and aversion is occurring as the animal makes the decision whether to continue consuming or seeking EtOH.…”
mentioning
confidence: 99%